Assessing the impact of global warming on the sport, tourism, and recreation industries in western Norway - Korsan-Kumińska , Karolina (Studia Ecologiae et Bioethicae, 2016)
Sport, tourism, and recreation, like many other areas of life, are influenced by environmental factors, including climate. Climate is one of the major factors determining the living conditions on our planet, which determine the functioning and behavior of all organisms. Therefore, this poses the question: Are global climate changes seen by ordinary people? If so, how are they seen and how do they affect the various domains of life, in particular, sport, tourism, and recreation? The aim of the pilot research was to determine the impact of global climate changes (observed in the public media as well as being in the public consciousness) in the area of western Norway (WN) on sport, tourism, and recreation. Pilot research was conducted in the summer and autumn of 2015 using a diagnostic survey on the internet. The research tool was a questionnaire survey. Respondents came from two groups: 61 employees and entrepreneurs in the industries of sport, tourism, and recreation in WN and 32 people either actively partaking in sport and recreational activities or visiting the region as tourists. Interviewees noted that climate changes have already occurred in the nature of western Norway. However most of them are not prepared for these changes even though they believe that the majority of the changes will only grow and intensify. For example, some of the researched companies have already been forced to take certain steps in relation to the companies functioning e.g., company reorganizations. The expected transformation in nature caused by global climate changes are changing the behavior of athletes, tourists, residents, representatives of the authorities, and economic entrepreneurs who make their living from tourism, recreation, and sport. In the future, Norway may turn out to be no longer as attractive as it is now for these people.